Understanding the robotization landscape transformation: A centering resonance analysis - Vijaya Lakshmi; Bouchaib Bahli (Journal of Innovation & Knowledge (JIK), 2020)
The ever-increasing worldwide demand for automation has augmented the adoption of technologies such as artificial intelligence and machine learning for industrial developments. Among the recent technological advancements, intelligent robots are increasingly becoming an integral part of several firms. The study focuses on the impact of intelligent robots on productivity, competitiveness and how firms are leveraging automation. This study uses centering resonance analysis (CRA) to develop an empirically grounded understanding of the rationale for robotization, through secondary archived data. Through the content analysis of over 261 online published articles, we decipher the derived themes through the following theoretical frameworks: behavioral, economic, and operations management perspectives. The findings suggest that firms are leveraging the concept of robotization to increase performance, efficiency, and profit. The deployment of robots in various firm domains focuses on public welfare, consumer orientation, and a sustainable environment and agriculture.
Keywords: M15; O31; Q55; 650; Automation; Centering resonance analysis; Empirical study; Robotization; Text-mining